MENINGKATKAN HASIL BELAJAR LUAS DAERAH BANGUN DATAR DENGAN MODEL PROBLEM BASED LEARNING - Naila Lutfiana; Sunarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to improve the mathematics learning outcomes of fourth-grade students at Elementary School of Benua Anyar 10 Banjarmasin through the implementation of the Problem Based Learning (PBL) model combined with a scientific approach. This research employed Classroom Action Research (CAR) conducted in two cycles. The subjects of the study were 15 fourth-grade students, consisting of 8 boys and 7 girls. Data were collected using observation sheets and learning outcome tests, and analyzed using descriptive quantitative and qualitative methods. The findings revealed that the Problem Based Learning model effectively enhanced students' learning outcomes in the topic of area of plane figures. During the pre-cycle stage, only 8 students (53.33%) met the minimum mastery criteria. In the first cycle, the number increased to 11 students (73.33%), and in the second cycle, 14 students (93.33%) achieved mastery. This research was considered successful, as it met the success indicator of at least 80% of students scoring above the minimum passing grade of 70.